ANALISIS POTENSI DAN DAYA SAING KECAMATAN SEBAGAI PUSAT PERTUMBUHAN SATUAN WILAYAH PENGEMBANGAN (SWP) KABUPATEN MALANG - Sutikno, -; Maryunani, - (Journal of Indonesian Applied Economics, 2007)
In terms of administration, Malang is divided into two regions, Malang City andMalang Regency. Although the regions are different, economically two regionscan not  separated because almost all economic activities are concentrated atMalang City. This has  impacts on the economic gap between Malang City andMalang Regency. With respect to gap, the research was conducted  to analyze thegrowth center of Regional Development Unit (RDU) of the Malang City, based ontwo development directions:  identifying sectoral economic potentials and  thatfor regional sowol potentials.In terms of regional aspects, the description of development centers in each RDUare: (1) Ngantang Sub-district is a priority for the development center of RDU I;(2) Singosari Sub-district  is a  priority  for  the development center of northernRDU  II;  (3) Pakisaji  Sub-district  is  a  priority  for  the  development  center  ofsouthern RDU II; (4) Poncokusumo Sub-district is a priority for the developmentcenter of RDU IV;  (5) Kepanjen Sub-district  is a priority  for  the developmentcenter of RDU V;  (6) Pagelaran Sub-district  is a priority  for  the developmentcenter of RDU VII; and (7) Turen Sub-district is a priority for the developmentcenter of RDU VIII.Since  the  results  has  policy  impacts,  the  government  of  the Malang Regencyshould  decide  regional  development  policies  referring  to  the  regionaldevelopment concept based on the economic and regional potentials so that itcan give priorities to potential districts to be acted as development centers. Byimplementing  the  policy,  it  is  expected  that  economic  activities will  not  beconcentrated on one development point, the Malang City as the only developmentpoint.Keywords: growth center, Regional Development Unit (RDU), sectoral economicpotentials and regional potentials